Silica nanofluid flooding for enhanced oil recovery in sandstone rocks - Magda I. Youssif; Rehab M. El-Maghraby; Sayed M. Saleh; Ahmed Elgibaly (Egyptian Journal of Petroleum)
Enhanced oil recovery is proposed as a solution for declining oil production. One of the advanced trends in the petroleum industry is the application of nanotechnology for enhanced oil recovery. Silica nanoparticles (SiNPs) are believed to have the ability to improve oil production, while being environmentally friendly and of natural composition to sandstone oil reservoirs.In our work, we investigated the effect of silica nanoparticles flooding on the amount of oil recovered. Experiments were carried using commercial silica of approximately 20 nm in size. We used sandstone cores in the core flooding experiments. For one of the cores tertiary recovery is applied where brine imbibition was followed by nanofluid imbibition. While in the other cores secondary recovery was applied where primary drainage is directly followed by nanofluid imbibition. We investigated the effect of concentration of nanofluid on recovery; in addition, residual oil saturation was obtained to get the displacement efficiency. Silica nanofluid of concentration 0.01 wt%, 0.05 wt%, 0.1 wt% and 0.5 wt% were studied.The recovery factor improved with increasing the silica nanofluid concentration until optimum concentration was reached. The maximum oil recovery was achieved at optimum silica nanoparticles concentration of 0.1 wt%. The ultimate recovery of initial oil in place increased by 13.28% when using tertiary flooding of silica nanofluid compared to the recovery achieved by water flooding alone. Based on our experimental study, permeability impairment was investigated by studying the silica nanoparticles concentration, and the silica nanofluid injection rate. The permeability was measured before and after nanofluid injection. This helped us to understand the behavior of the silica nanoparticles in porous media. Results showed that silica nanofluid flooding is a potential tertiary enhanced oil recovery method after water flooding has ceased. Keywords: Enhanced oil recovery (EOR), Porous media, Dispersed silica nanoparticle, Nanoflooding, Nanoparticles stability, Nanofluid